Pre-operative glycaemic control and long-term survival in diabetic patients after coronary artery bypass grafting. (10th May 2021) - Deo, Salil; Sundaram, Varun; Sheikh, Muhammad Adil; Sahadevan, Jayakumar; Selvaganesan, Padmini; Madan Mohan, Sri Krishna; Rubelowsky, Joseph; Elgudin, Yakov; Josephson, Richard; Davierwala, Piroze M; Cmolik, Brian
Abstract:  : OBJECTIVES: We analysed the Veteran Affairs data to evaluate the association of pre-operative glycated haemoglobin (HbA1c) and long-term outcome after isolated coronary artery bypass grafting (CABG). METHODS: Veterans with diabetes mellitus and isolated CABG (2006–2018) were divided into 4 groups (I: HbA1c <6.5%, II: HbA1c 6.5–8, III 8–10% and IV: HbA1c >10%). The relationship of pre-operative HbA1c and long-term survival was evaluated with a multivariable Cox proportional hazards model and reported as hazard ratios (HR). The cumulative incidence of secondary end-points [myocardial infarction (MI) and repeat revascularization (percutaneous intervention)] for each group was modelled as competing events with cause-specific Cox proportional hazards models. RESULTS: Overall, 16 190 patients (mean age 64.9 years, male 98%; insulin dependent 53%) with diabetes mellitus underwent isolated CABG. We observed 19.4%, 45.4%, 27% and 8.2% patients in groups I, II, III and IV, respectively. Patients with HbA1c >10% were the youngest (mean age 60.9 years) and had high rates of Insulin dependence (78%). In patients with HbA1c >10%, improvement in levels was observed in 76%. The median follow-up observed was 5.8 (3.2–8.8) years. Compared to the study mean HbA1c (7.3%), mortality rate increased with HbA1c levels >8%, and especially with pre-operative HbA1c levels >9%. Compared to patients with HbA1c <8%, HbA1c 8–10% and >10% were associated with increased MI (HR 1.24 and HR 1.39, respectively) and need for reintervention (HR 1.20 and HR 1.24, respectively). CONCLUSIONS: In patients undergoing CABG, pre-operative HbA1c >8% is associated with the increased risk of mortality and adverse cardiac events.